2020
DOI: 10.3390/antiox9020178
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Insight upon Chitosan Solution and Chitosan Nanoparticles Application on the Phenolic Content, Antioxidant and Antimicrobial Activities of Individual Grape Components of Sousão Variety

Abstract: Chitosan, a natural polysaccharide, has been previously proposed as an elicitor in plants to prevent pathogen infections. The present study aimed to analyze the effect of chitosan solution and chitosan nanoparticles treatment applied on the grapevine variety Sousão with respect to the phenolic composition, antioxidant potential and antibacterial activity of its individual grape components. Grapevine plants of selected lines were sprayed with chitosan solution and chitosan nanoparticles, and ethanolic extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 46 publications
(61 reference statements)
0
29
0
1
Order By: Relevance
“…It has often been reported that polyphenolic extracts are more efficient against Gram-positive bacteria [12]. Cell walls of Gramnegative represent a major barrier for the entry of phenolic compounds into cell cytoplasm due to the repulsion between lipopolysaccharide found in the surfaces of Gram-negative bacteria and phenols [13]. However, in this study, phenolic extracts did not have any effect against two Gram-positive bacteria (E. faecium and E. faecalis) and one Gram-negative bacteria (S. enteritidis).…”
Section: Resultsmentioning
confidence: 99%
“…It has often been reported that polyphenolic extracts are more efficient against Gram-positive bacteria [12]. Cell walls of Gramnegative represent a major barrier for the entry of phenolic compounds into cell cytoplasm due to the repulsion between lipopolysaccharide found in the surfaces of Gram-negative bacteria and phenols [13]. However, in this study, phenolic extracts did not have any effect against two Gram-positive bacteria (E. faecium and E. faecalis) and one Gram-negative bacteria (S. enteritidis).…”
Section: Resultsmentioning
confidence: 99%
“…Phytohormonal control has also been suggested as another strategy since hormones such as ABA, ethylene, brassinosteroids or gibberellins provide many signals for the onset of ripening [4,47,48]. Other compounds known as elicitors such as benzothiadiazole, methyl jasmonate, chitosan and yeast extract, have demonstrated their efficacy for increasing grape phenolic content [49][50][51]. HB treatments could somehow be activating ethylene biosynthesis in grapevines, therefore promoting the anthocyanin accumulation in a similar manner to the positive control (FRUITEL; [52]).…”
Section: Discussionmentioning
confidence: 99%
“…Also Ferri et al (2009) stated that Chitosan increases the anthocyanins in berry skin. Silva et al (2020) noticed an increment in anthocyanin recorded from the application of Chitosan Nano-particles.…”
Section: Total Anthocyanin Content In Berry Skinmentioning
confidence: 98%